Participation in residential child care in Germany - Bernhard Babic; Liane Pluto (Scottish Journal of Residential Child Care)
This paper sets out to examine how participation is perceived and enacted in German residential child care. Residential child care varies considerably in Germany. Mostly, residential establishments consist of four or five units which cater for between six and eight young people of different ages and mixed sex. Care is normally provided in shifts by teams of four to five staff. Residential establishments, however, may consist of small groups based on a family-type structure (e.g. children's villages). Other residential units are integrated in 'normal' residential areas which are not directly linked to a larger facility. Yet others may be supported-living units for individuals (Freigang & Wolf, 2001). Residential establishments in Germany combine everyday life with educational and therapeutic services in order that they either seek to ensure the return of the child or young person to his or her own family, or prepare them for living in another family. They can also provide long-term care and prepare the young person for independent living. In legal terms, these three goals are equivalent. In actual practice, a speedy return to the family is the preferred choice, not least for cost reasons.